Cancer in the Arab World - Al-Shamsi, Humaid O.; Abu-Gheida, Ibrahim H.; Iqbal, Faryal; Al-Awadhi, Aydah (Springer Nature, 2022)
This is an Open Access book. This book is a must-have for healthcare providers and researchers, public health specialists and policy makers who are interested and involved in cancer care in the Arab world. The Arab world consists of 22 countries, which are members of the Arab League and spanning over 13,132,327 km2 with over 423,000,000 population. Over the past few decades, the Arab world has witnessed a swift evolution in healthcare provision. Nonetheless, Arab countries have considerable variability in economic capabilities, resource allocation, and intellectual talent that inevitably reflect on access to modern cancer care and prevention. This book is authored by experts from the Arab world who provide vital information on cancer statistics and risk factors, available clinical care pathways and infrastructure, and prevention programs in their individual countries. The chapters also address specific challenges in each country and insights into future directions to achieve optimal care with conventional and novel diagnostics and therapies to keep up with the era of precision medicine. Special topics of interest and unique to the Arab world are also discussed, such as out of the country's medical tourism for cancer care and cancer care during war and conflict. Other special chapters include: Cancer research in the Arab world, Radiation therapy in Arab World and Pediatric Oncology in the Arab World Cancer in the Arab World is the first comprehensive book that addresses cancer care in depth in all Arab countries and it is endorsed by the prestigious Emirates Oncology Society.